1999
DOI: 10.1080/00405009908690625
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Water-quenching on the Electrostatic Charging of Fibers and Fabrics during the Melt-blowing Process

Abstract: This paper considers the efficiency of electrostatic charging of water-sprayed fibers during the melt-hiowing process. Two charging methods were used to charge the flbers near the die exit and the fabrics after the collector. Both showed that the charging efficiency was not affected hy the water-spraying process if the amount of spraying was controlled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In 1999, a paper concerned the efficiency of electrostatic charging of water-sprayed fibers during the melt-blowing process was published. It was found that the charging efficiency was not affected by the water-spraying process if the amount of spraying was controlled 9 . In 2014, a paper in Korean was published about the melt-blown nonwoven filter for medical masks manufactured using an online triboelectric charging system 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In 1999, a paper concerned the efficiency of electrostatic charging of water-sprayed fibers during the melt-blowing process was published. It was found that the charging efficiency was not affected by the water-spraying process if the amount of spraying was controlled 9 . In 2014, a paper in Korean was published about the melt-blown nonwoven filter for medical masks manufactured using an online triboelectric charging system 10 .…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the charging efficiency was not affected by the water-spraying process if the amount of spraying was controlled. 7 In 2014, a paper in Korean was published about meltblown nonwoven fabric filters for medical masks by using an online hydro charging system. 8 The effects of the basis weight of meltblown nonwoven fabrics and die-to-collector distance on the filtration performance of meltblown nonwoven fabrics were investigated, while there was no deep discussion about the charge origin of the hydro charging treatment.…”
mentioning
confidence: 99%